An Unexpected Anemia Hiding a Rare Syndrome With Overlapping Phenotypes. Issue 11 (24th November 2022) - Dal Buono, Arianna; Poliani, Laura; Repici, Alessandro; Hassan, Cesare; Bianchi, Paolo
ABSTRACT: Gastric polyposis is a rare endoscopic finding that can imply genetic syndromes predisposing to cancer development. Among the possible conditions associated with gastric polyposis and early onset gastric cancer (younger than 45 years) is juvenile polyposis syndrome. We present a clinical case of early onset gastric cancer associated with a frameshift mutation in the gene SMAD4 . Individuals carrying a pathogenic variant of this gene have a high risk of malignant transformation, especially of gastric cancer. Moreover, most of these patients present also with extraintestinal features of the hereditary hemorrhagic telangiectasia, and the first symptom prompting medical evaluation is anemia.